FEATURES OF STUDENT LEARNING MOTIVATION (Web of Teachers: Inderscience Research, 2024)
The article describes the approaches to examining educational motivation, modern challenges, and issues related to learning motivation, and outlines the quantitative and qualitative indicators of educational quality.